Strategic IT Alignment and Organizational Agility in Nonprofits during Crisis - Lauren Azevedo; Roderick Lee; Wanzhu Shi (Administrative Sciences, 2024)
As the study of nonprofit organizations and their operating environment has become increasingly interdisciplinary, scholars have leveraged business strategies to increase knowledge and improve performance. This study considers how strategic information technology alignment can impact organizational agility among nonprofits that are in the midst of the COVID-19 pandemic, a dynamic and complex crisis environment. Using a survey of United States-based nonprofits, we find that organizational alignment as well as aspects of financial stability significantly impact organizational agility. This study concludes with implications for nonprofits to broaden their participation in a digital society by developing their capacity to strategically plan, design, and implement strategic initiatives that align the organizational mission and assist with agility. Further, a broader discussion on the need to expand the definition of alignment in the context of nonprofit organizations is made, particularly in regard to new initiatives to include underrepresented groups and diverse voices in strategic initiatives.